Development and Evaluation of Laboratory Work Module to Enhance Student’s Knowledge in Molecular Visualization - Fitri, Nur Aini; Hidayanti, Ermia; Hadisaputra, Saprizal; Han, Sha-Ling (JTK (Jurnal Tadris Kimiya), 2023)
This study aims to assess the validity and practicality of computational chemistry practicum modules for high school students, focusing on molecular geometry and independent learning. The research used a Research and Development (R&D) approach with the 4D model (define, design, develop, and disseminate). A limited trial was conducted with 23 students selected through cluster random sampling. The module development research results show that the validity assessed using Aiken’s V index by two validators yielded a value of 0.64, indicating its validity and suitability for high school students. Furthermore, the practicality of the module was evaluated using a student response questionnaire, which yielded an average score of 84%, indicating its high practicality. Consequently, the module is considered valid and highly practical as a practicum learning resource for high school students.